Magnetic Resonance Relaxation Anisotropy: Physical Principles and Uses in Microstructure Imaging - Knight, Michael J. (Biophys J, 2017)
Magnetic resonance imaging (MRI) provides an excellent means of studying tissue microstructure noninvasively since the microscopic tissue environment is imprinted on the MRI signal even at macroscopic voxel level. Mesoscopic variations in magnetic field, created by microstructure, influence the transverse relaxation time (T(2)) in an orientation-dependent fashion (T(2) is anisotropic). However, predicting the effects of microstructure upon MRI observables is challenging and requires theoretical insight. We provide a formalism for calculating the effects upon T(2) of tissue microstructure, using a model of cylindrical magnetic field perturbers. In a cohort of clinically healthy adults, we show that the angular information in spin-echo T(2) is consistent with this model. We show that T(2) in brain white matter of nondemented volunteers follows a U-shaped trajectory with age, passing its minimum at an age of ∼30 but that this depends on the particular white matter tract. The anisotropy of T(2) also interacts with age and declines with increasing age. Late-myelinating white matter is more susceptible to age-related change than early-myelinating white matter, consistent with the retrogenesis hypothesis. T(2) mapping may therefore be incorporated into microstructural imaging.